2015
DOI: 10.1002/advs.201500100
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystalline Rhodium Nanosheets with Atomic Thickness

Abstract: CO confinement strategy for ultrathin Rh nanosheets: CO is introduced as a confining agent to regulate the anisotropic growth of unique 2D structure. The single‐crystalline Rh nanosheets have a thickness of three to five atomic layers and tunable edge length ranging from 500 to 1300 nm. By understanding the formation mechanism, surface‐clean Rh nanosheets are also prepared and display better catalytic performance that their surfactant‐capped nanosheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 40 publications
2
97
0
Order By: Relevance
“…The previous excellent studies have demonstrated that the atoms at defect sites with low-coordination numbers are super active for the various catalytic reactions. 22,23,25 Compared with bulk metal nanoparticles, the atomically thick ultrathin nanoplates maximize the number of coordinately unsaturated active sites in the edges and exposed faces (Supplementary Scheme S2) that have an essential role in catalytic reactions. 22,25,52,53 The atomic force microscopic image indicates that the thickness of the 2D Rh nanoplate is only approximately 1.2 nm (Figure 1i), and the nanoplate contains only approximately four atomic layers.…”
Section: Light-enhanced Catalytic Activity For the Hgr-n 2 Hmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous excellent studies have demonstrated that the atoms at defect sites with low-coordination numbers are super active for the various catalytic reactions. 22,23,25 Compared with bulk metal nanoparticles, the atomically thick ultrathin nanoplates maximize the number of coordinately unsaturated active sites in the edges and exposed faces (Supplementary Scheme S2) that have an essential role in catalytic reactions. 22,25,52,53 The atomic force microscopic image indicates that the thickness of the 2D Rh nanoplate is only approximately 1.2 nm (Figure 1i), and the nanoplate contains only approximately four atomic layers.…”
Section: Light-enhanced Catalytic Activity For the Hgr-n 2 Hmentioning
confidence: 99%
“…22,23,25 Compared with bulk metal nanoparticles, the atomically thick ultrathin nanoplates maximize the number of coordinately unsaturated active sites in the edges and exposed faces (Supplementary Scheme S2) that have an essential role in catalytic reactions. 22,25,52,53 The atomic force microscopic image indicates that the thickness of the 2D Rh nanoplate is only approximately 1.2 nm (Figure 1i), and the nanoplate contains only approximately four atomic layers. As an intrinsic property of ultrathin nanoplates, Au@Rh core-shell nanodendrites contain numerous Rh atoms at defect sites with low-coordination numbers because nearly half of the Rh atoms are present on the surface of the Rh nanoplates with four atomic layers.…”
Section: Light-enhanced Catalytic Activity For the Hgr-n 2 Hmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20]26 ] Unfortunately, because of the nondirectional nature of most metallic bonds, metallic atoms exhibit a strong tendency to form close-packed structures in three dimensions. [ 25,27,28,[30][31][32][33][34][35][36][37][38] Recent study showed signifi cant progress that 2D single-atom-thick Fe membranes formed in graphene perforations from the FeCl 3 immersion solution. In the past decades, traditional vapor deposition techniques have achieved signifi cant progress in the controllable fabrication of thin metal fi lms with thickness down to only a few nanometers.…”
mentioning
confidence: 99%
“…[9] In particular, their high density of surface atoms and am yriad of unsaturated surface coordinationc oulds ignificantly improve the utilization of noble metal atoms ando ffer plentya ccessiblee lectrochemically active sites. [10] However,t he growth and stabilization of 2D noble-metal-basedn anosheets are still fairly challenging, since noble metals form non-layer-structured materials, preferably close-packed crystalline structures, and the unsaturated surface coordination is quite unstable. [11] Furthermore, most of the previously reported noble-metal-based nanosheets are rigid nanostructures with smooth and flat surfaces, which tend to be agglomerated irreversibly during materialf abrication and catalytic processes,l eadingt oadetrimentall oss of accessible surface atoms.…”
mentioning
confidence: 99%